1990
DOI: 10.1007/bf00591410
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic dilation of colonic postoperative strictures

Abstract: After the use of surgical staplers had become widespread, the number of colonic postoperative stenoses was observed to have increased. Nevertheless, the clinical relevance of this observation is minimal since only 2-5% of the patients complain of chronic constipation or obstruction symptoms. In such cases medical therapy is somewhat troublesome, and surgical treatment always implies a major operation. Endoscopic dilation has proved to be a reliable, simple, and safe therapeutic alternative. Forty-two patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…We can only speculate on the true contributory significance of these factors for stricture formation since comparisons with the patients who recovered uneventfully without developing an anastomotic stricture are not available. The relevance of these factors remains controversial, and no prospective studies are currently under way [5,10,16].…”
Section: Discussionmentioning
confidence: 97%
“…We can only speculate on the true contributory significance of these factors for stricture formation since comparisons with the patients who recovered uneventfully without developing an anastomotic stricture are not available. The relevance of these factors remains controversial, and no prospective studies are currently under way [5,10,16].…”
Section: Discussionmentioning
confidence: 97%
“…Die Anastomosenstenosen k6nnen nach Jahrzehnten auftreten, h/iufig sind sie aber in den ersten 6 Monaten postoperativ zu beobachten [14,15]. Bei unseren 21 Patienten wurde die Anastomosenstenose 3-12 Monate postoperativ diagnostiziert.…”
Section: Lokalisation Der Stenosenunclassified
“…Skreden et al [10] reported that symptomatic relief was obtained in 10 of 11 patients (90.9%) with 10 (SD 7, range 1-24) months of followup, and the remaining patient 'had diarrhoea until death from cardiac failure a year later' . Pietropaolo et al [14] reported a failure rate of 2.4% (1/42) in their series. They also concluded that success of a single session of endoscopic dilatation (76.9%) was significantly higher than bougienage (51.8%).…”
Section: Relief Of Symptomsmentioning
confidence: 99%
“…The rest of the patients underwent laser incision only (12/94, 12.7%) or bougienage (4/94, 4%) as treatment of stricture. Di Giorgio et al [6] compared endoscopic with fluoroscopic dilatation in a prospective comparative study and Pietropaolo et al [14] compared endoscopic dilatation with bougienage (table 2). Outcomes Dilatation of strictures was not associated with any mortality.…”
Section: Methodsmentioning
confidence: 99%